Cloning of antifungal gene from Bacillus licheniformis by application of low energy ion beam bombardment - Mahadtanapuk S. (2014)
This work was aimed at locating the gene involved in antifungal ability of bacterium Bacillus licheniformis into yeast by application of low energy ion beam. Nitrogen ions were used to bombard the bacterial cells under vacuum condition at energy 30 keV with a fluence of 1016 ions/cm2. The HAT-RAPD marker revealed the modified polymorphism fragment (615 bp) presenting in the wild type but not in the bacterial mutant. This fragment was subcloned into pGEM-T easy vector and then sequenced. When the sequence of this fragment was compared with those already contained in the database, the fragment was found to be related to the lipase gene. In order to transfer the full gene, the amplified fragment of 615 bp was subcloned into a high expression vector, pYES2. Low energy ion beam was applied again but for the gene transfer into the Saccharomyces cerevisiae strain W303C. Nitrogen ions bombarded the yeast cells under vacuum condition at an energy of 50 keV with ion fluences of 5-20 × 1015 ions/cm2. After the treatment, the cells were screened by medium selection and restriction enzymes. The putative gene was expressed in yeast and the ability of the protein was observed by Dual culture technique with inhibition of plant disease fungal. The results provided evidence for the presence of the useful gene in the final product yeast with the assistance of low energy ion beams. © 2009 Elsevier B.V.